CLINICAL FEATURES OF JUVENILE IDIOPATHIC ARTHRITIS IN CHILDREN - Khamraeva Dilnoza Razzakovna (Modern American Journals, 2025)
The article describes the clinical features of juvenile idiopathic arthritis in children living in the Bukhara region. The clinical features of the disease and the results of laboratory analysis are important when making a diagnosis and choosing an effective treatment method. An effective treatment method is characterized by a faster onset of remission, prolongation of its duration and reduction of side effects of drug treatment.
Keywords: children, juvenile arthritis, joint, diagnosis.